A sectional critical plane model for multiaxial high‐cycle fatigue life prediction. Issue 3 (12th December 2020) - Qi, Xinxin; Liu, Tianqi; Shi, Xinhong; Wang, Jiaying; Zhang, Jianyu; Fei, Binjun
Abstract: A stress‐based sectional critical plane model is proposed to predict fatigue life under multiaxial constant amplitude loading. The proposed model considers the effects of material properties and loading paths including stress amplitude ratio, phase angle and mean stress. By introducing the ratio of maximum shear stress amplitude to maximum normal stress amplitude, the crack behaviour can be predicted and the critical planes can be divided into three sections: the maximum normal stress plane, maximum damage plane and maximum shear stress amplitude plane. To verify the accuracy and applicability of the proposed model, experimental data of 30CrMnSiA steel conducted by the authors and other test data of different materials from the existing literatures are utilized. The prediction results demonstrate that the proposed sectional critical plane model shows strong applicability for steel, aluminium and titanium alloy materials, especially under the multiaxial loadings with mean stresses. For steel materials, the prediction results of the proposed model are better than the commonly used criteria.